The Role of Seha’s Telepharmacy in Meeting Patient Expectations for Medication Counseling - Mohammad Ahmed Gamaruddin,; Rahma Saud Bukhari,; Nasser Motlaq AlQuthami,; Naif Mohammed Ahmed Babakour,; Asma Ahmad Younis,; Sultan Saed Alharthi,; Majed Hamdan Albeshri,; Khalid Abdulalli Alsubhi,; Turki Ahmed Almoabdi,; Yahya Obedullah Alsobhi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
This study examines Seha’s telepharmacy service, focusing on its role in meeting patient expectations for medication counseling. The objective of the studyincludes measuring patient satisfaction, knowing the efficiency of telepharmacy in increasing the access level, and measuring the quality of counseling. Self-administered questionnaires were employed to collect data for the satisfaction and counseling from participants and results were analyzed using quantitative research findings. Furthermore, the findings obtained have noted high levels of patient satisfaction owing to telepharmacy and noted the enhanced convenience experienced by patients. Still, the following points of concern were raised concerning personalised communication. Altogether, Seha’s telepharmacy is sufficiently satisfactory to meet the patient expectations, and can be considered as a beneficial remote substitution to the medication counseling in healthcare.